2019
DOI: 10.3390/su11164311
|View full text |Cite
|
Sign up to set email alerts
|

How Does Customer–Company Identification Enhance Customer Voice Behavior? A Moderated Mediation Model

Abstract: For sustainable development, enterprises need to establish a good relationship with customers. Existing studies have pointed out that customer voice behavior is beneficial to maintaining and developing customer–firm relationships. Based on social identity theory, social exchange theory and self-efficacy theory, we propose a moderated mediation model to analyze the impact of customer–company identification on customer voice behavior, which includes complaints and suggestions for service improvement. Data were c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0
6

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(30 citation statements)
references
References 62 publications
1
23
0
6
Order By: Relevance
“…CCI is an established concept and is a way to build a deep and enduring relationship with the customers (Huang and Cheng, 2016;Weng and Cheng, 2019;Abernethy et al, 2019). The term CCI is coined by Mael and Ashforth (1992), as then it is linked to customer loyalty and customer engagement (Badenes-Rocha et al, 2019), customer citizenship behavior (Hur et al, 2018), employees pro-environmental behavior (Cheema et al, 2019;Afsar et al, 2018) and customer voice behavior (Ran and Zhou, 2019). Identification with a company strengthens the affective relationship between customers, employees and their organization based on the cognitive concept of perceived oneness (Tufan and Wendt, 2020).…”
Section: Electronic-service Quality and Customer-company Identificationmentioning
confidence: 99%
“…CCI is an established concept and is a way to build a deep and enduring relationship with the customers (Huang and Cheng, 2016;Weng and Cheng, 2019;Abernethy et al, 2019). The term CCI is coined by Mael and Ashforth (1992), as then it is linked to customer loyalty and customer engagement (Badenes-Rocha et al, 2019), customer citizenship behavior (Hur et al, 2018), employees pro-environmental behavior (Cheema et al, 2019;Afsar et al, 2018) and customer voice behavior (Ran and Zhou, 2019). Identification with a company strengthens the affective relationship between customers, employees and their organization based on the cognitive concept of perceived oneness (Tufan and Wendt, 2020).…”
Section: Electronic-service Quality and Customer-company Identificationmentioning
confidence: 99%
“…The underlying mechanism of customer voice behaviors are increasingly investigated by highlighting the roles of customer inclusion, identification, and the perceived trustworthiness and power of service workers ( Bove and Robertson, 2005 ; Béal and Sabadie, 2018 ; Ran and Zhou, 2019 ). However, existing studies have four clear drawbacks.…”
Section: Introductionmentioning
confidence: 99%
“…In those studies, complaints and suggestions are all customer voices ( Cossío-Silva et al, 2016 ; Béal and Sabadie, 2018 ). In general, the two terms are mixed in usage ( Boote, 1998 ; Béal and Sabadie, 2018 ; Ran and Zhou, 2019 ), which casts a negative light on the understanding of the underlying mechanisms of these two behaviors. Therefore, the essential differences of the two constructs require clear explanation.…”
Section: Introductionmentioning
confidence: 99%
“…Although prior studies show findings of the firm complaint (Lu et. al., 2018;Ran and Zhou, 2019;Ndofirepi, 2020) or 3rd party complaint (Moreira and Silva, 2016) apart, the current study contributes to the existing service recovery literature by examining the joint direct and indirect effects of firm reputation and post-failure negative emotions after a service failure on the voice complaint choice of bank customers to the firm and a 3rd party. More specifically, we first focused on whether firm reputation and negative emotions cause a difference in the complaint choices of customers.…”
Section: Theoretical Implicationsmentioning
confidence: 98%
“…Having established the importance of understanding direct firm complaints, some studies examined and found that constructs, such as perceived costs and benefits of complaining (Richins, 1980;Lu et al, 2018;Mei et al, 2019), ease of complaining (Tax and Brown, 1998;Sirisena, 2019), the likelihood of success in complaining (McKee et al, 2006;Blodgett et.al., 2018;Ndofirepi, 2020), and complaint self-efficacy (Susskind, 2000;Ran and Zhou, 2019), may significantly influence consumers' decisions to complain directly to the business.…”
Section: Customer Complaint Behaviormentioning
confidence: 99%